Bio-inspired Aerodynamic Noise Control: A Bibliographic Review - Bennett, Gareth (My University, 2019)
It is well-known that many species of owl have the unique ability to fly silently, which can be attributed to their distinctive and special feather adaptations. Inspired by the owls, researchers attempted to reduce the aerodynamic noise of aircraft and other structures by learning their noise reduction features from different viewpoints and then using the gained knowledge to develop a number of innovative noise reduction solutions. Although fruitful results have been achieved in the bio-inspired aerodynamic noise control, as far as the authors know, comparatively little work has been done to summarize the main findings and progresses in this area. In this bibliographic survey, we systematically review the progresses and trends of the bio-inspired aerodynamic noise control, including the macroscopic and microscopic morphological characteristics of the owl wing feathers, the noise measurements on both flying birds in the field and prepared wings in the wind tunnel, as well as theoretical, numerical and experimental studies that explored the feasibility, parameter influence, aerodynamic effects and underlying mechanisms of the four main bio-inspired noise reduction techniques, i.e., leading edge serrations, trailing edge serrations, fringe-type trailing edge extensions and porous material inspired noise reduction. Finally, we also give some suggestions for future work.
PUBLISHED
Paper Number: 2224. MDPI, Special Issue "Airframe Noise and Airframe/Propulsion Integration"
Keywords: Bionics; Aerodynamic noise control; Leading edge serrations; Trailing edge serrations; Fringe-type trailing edge; Porous material; Smart & Sustainable Planet